RFID Authentication Protocols Based on Error- Correcting Codes: A Survey - Chikouche, Noureddine; Cherif, Foudil; Cayrel, Pierre-Louis; Benmohammed, Mohamed (Université de M'sila, 2017)
Code-based cryptography is a very promising research area. It allows the construction of different cryptographic mechanisms (e.g. identification protocol, public-key cryptosystem, etc.). McEliece cryptosystem is the first code-based public-key cryptosystem; several variants of this cryptosystem were proposed to design various security protocols in different systems. In this paper, we present a survey on various and recent authentication protocols in radio frequency identification systems which use diverse variants of the McEliece cryptosystem. Moreover, we discuss the security and the performance of each presented protocol.
Keywords: RFID Error-correcting codes Authentication protocols Vulnerabilities